THE PROBLEMATICS OF JAD MAAL IKHWAH: PERSPECTIVES OF IBN ABBAS AND ZAID IBN TSABIT - Fadlan Harmein Harahap; Muhammad Iqbal Irham; Muhammad Syahnan (Journal Analytica Islamica, 2026)
Jad maʿal ikhwah refers to an inheritance issue that arose after the death of the Prophet Muhammad, particularly during the caliphate of ʿUmar ibn al-Khaṭṭab. In this case, full siblings and the paternal grandfather are two heirs who claim a share of the inheritance. According to the science of faraʾiḍ, only one of these parties is entitled to inherit, while the other is excluded. Both are considered ʿasabah heirs, meaning they are entitled to the residual estate after the fixed shares have been distributed. Ibn ʿAbbas held the view that only the grandfather is entitled to inherit in such cases, whereas Zayd ibn Thabit argued that both the grandfather and the full siblings are entitled to share the inheritance. This study employs qualitative and normative analysis of legal norms and juristic opinions found in both classical and contemporary fiqh texts. The findings indicate that the view of Zayd ibn Thabit, which grants inheritance rights to both the grandfather and the full siblings simultaneously, has been widely accepted by jurists and remains relevant in contemporary contexts.